Human centromeres produce chromosome-specific and array-specific alpha satellite transcripts that are complexed with CENP-A and CENP-C - McNulty, Shannon M. (Dev Cell, 2017)
Human centromeres are defined by alpha satellite DNA arrays that are distinct and chromosome-specific. Most human chromosomes contain multiple alpha satellite arrays that are competent for centromere assembly. Here, we show that human centromeres are defined by chromosome-specific RNAs linked to underlying organization of distinct alpha satellite arrays. Active and inactive arrays on the same chromosome produce discrete sets of transcripts in cis. Non-coding RNAs produced from active arrays are complexed with CENP-A and CENP-C, while inactive array transcripts associate with CENP-B and are generally less stable. Loss of CENP-A does not affect transcript abundance or stability. However, depletion of array-specific RNAs reduces CENP-A and CENP-C at the targeted centromere via faulty CENP-A loading, arresting cells before mitosis. This work shows that each human alpha satellite array produces a unique set of non-coding transcripts, and RNAs present at active centromeres are necessary for kinetochore assembly and cell cycle progression.